2021
DOI: 10.1021/acsomega.1c02405
|View full text |Cite
|
Sign up to set email alerts
|

Materials with Hierarchical Porosity Enhance the Stability of Infused Ionic Liquid Films

Abstract: Defined surface functionalities can control the properties of a material. The layer-by-layer method is an experimentally simple yet very versatile method to coat a surface with nanoscale precision. The method is widely used to either control the chemical properties of the surface via the introduction of functional moieties bound to the polymer or create nanoscale surface topographies if one polymeric species is replaced by a colloidal dispersion. Such roughness can enhance the stability of a liquid film on top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…As lubricants, beside silicone oil, we chose hexadecane, olive oil, and a phosphonium-based ionic liquid, tributylmethyl­phosphosphonium bis­(trifluoro­methylsulfonyl)­imide [TBMP]­[NTf 2 ], as representative examples of conventional hydrocarbon oils, natural oils, and ionic liquids (Figure ). The latter can be important for the design of repellent surfaces with long-term stability at elevated temperatures, and in the context of supported ionic liquid catalysis (SILP). The structural formula of olive oil, which is composed of multiple fatty acids, is simplified to oleic acid in Figure . As reactive species, we chose available molecules with a chemical structure matching that of the lubricant, but containing amino, thiol, or acid chloride groups.…”
Section: Resultsmentioning
confidence: 99%
“…As lubricants, beside silicone oil, we chose hexadecane, olive oil, and a phosphonium-based ionic liquid, tributylmethyl­phosphosphonium bis­(trifluoro­methylsulfonyl)­imide [TBMP]­[NTf 2 ], as representative examples of conventional hydrocarbon oils, natural oils, and ionic liquids (Figure ). The latter can be important for the design of repellent surfaces with long-term stability at elevated temperatures, and in the context of supported ionic liquid catalysis (SILP). The structural formula of olive oil, which is composed of multiple fatty acids, is simplified to oleic acid in Figure . As reactive species, we chose available molecules with a chemical structure matching that of the lubricant, but containing amino, thiol, or acid chloride groups.…”
Section: Resultsmentioning
confidence: 99%
“…For this specific application, the main goal is to obtain IOs with the most regular morphology achievable, and with a neck size that allows sufficient flow of substances for subsequential functionalization steps, taking into consideration the challenge of diffusion in IOs. 54 Note that as no photonic effect is exploited, the pore size is not limited to dimensions that would interact with light to form structural color, which is a common design criteria for IOs. 10,55 IOs with 350 nm pores showed the lowest number of cracks, the highest pore connectivity, and the highest surface-to-volume ratio at a fixed number of layers to enable comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The sacrificial polystyrene (PS) spheres used in this study were prepared following the protocol reported in the literature. [ 28,29 ]…”
Section: Methodsmentioning
confidence: 99%
“…The sacrificial polystyrene (PS) spheres used in this study were prepared following the protocol reported in the literature. [28,29] Anodization of aluminum into ordered pores: The generation of the tunable ordered porous system follows the standard two-step anodization procedure described in the literature. [30] A homemade setup was used to anodize four circular aluminum plates of 2.2 cm diameter, held by Orings underneath a polyvinyl chloride beaker.…”
Section: Methodsmentioning
confidence: 99%